2009
DOI: 10.1016/j.ahj.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A multifaceted intervention to improve blood pressure control: The Guideline Adherence for Heart Health (GLAD) study

Abstract: Background-Although high blood pressure is associated with significant morbidity and mortality, the proportion reaching the goal blood pressures as outlined in the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, Treatment of High Blood Pressure (JNC 7) is low. We conducted a randomized trial in primary care practices of a multifactorial intervention targeted to improve providers' adherence to hypertension guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Examples of effective strategies include home BP monitoring; in-person, telephone, or web-based motivational strategies delivered by a nurse and/ or a pharmacist; collaborative management by primary carepharmacist teams; 60,61 and involvement of community health workers as members of the care team. 62 Physician-directed interventions such as continuing medical education, academic detailing, quality review and feedback, and computer decision support/reminders to change prescribing behaviors, when used alone, have not shown improvements in health outcomes, [63][64][65][66][67][68] and few studies have focused on communication skills training skills for providers. 39,61 If shown to be effective in well-designed studies, integrating the best of these strategies will provide models that may be disseminated into practice to improve quality of care and reduce disparities in cardiovascular disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of effective strategies include home BP monitoring; in-person, telephone, or web-based motivational strategies delivered by a nurse and/ or a pharmacist; collaborative management by primary carepharmacist teams; 60,61 and involvement of community health workers as members of the care team. 62 Physician-directed interventions such as continuing medical education, academic detailing, quality review and feedback, and computer decision support/reminders to change prescribing behaviors, when used alone, have not shown improvements in health outcomes, [63][64][65][66][67][68] and few studies have focused on communication skills training skills for providers. 39,61 If shown to be effective in well-designed studies, integrating the best of these strategies will provide models that may be disseminated into practice to improve quality of care and reduce disparities in cardiovascular disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[10;11] However, the implementation of the intervention proved to be a challenge for several reasons. Provider turnover, technical issues with Palms requiring staff assistance, technology differences among practices, provider and practice schedules, and differences in provider familiarity with technology all proved to be challenges for which we had not originally planned.…”
Section: Discussionmentioning
confidence: 99%
“…I did a quick update of this review for the period 2004–2009 and found 16 randomized controlled trials; 6 of these targeted clinicians only, 3 targeted both clinicians and patients, and 7 targeted patients only. Studies that targeted clinicians only included continuing medical education, academic detailing, quality review and feedback, and computer decision support/reminders to change prescribing behaviors; none showed improvements in patient adherence or blood pressure control 111116 Table 2. shows the 10 studies that included patient interventions 117126.…”
Section: Questions and Discussionmentioning
confidence: 99%